Comparison of tooth substance loss and angle deviation in access cavity preparation using guided endodontics and conventional method in calcified canals - An in vitro study - Bansal, Rajinder Kumar; Bansal, Manu; Garg, Reeshu; Bansal, Dolphi (Journal of conservative dentistry, 2025)
Abstract Aims: This study aimed to evaluate the accuracy of access cavity preparation using guided endodontics (GE) and conventional technique (CT) in calcified canals. Subjects and Methods: Twenty teeth with calcification up to middle third were collected after scanning through RadioVisioGraphy (RVG). Preoperative cone-beam computed tomography (CBCT) scan was done and samples were randomly divided into two groups of ten samples each on the basis of method of access cavity preparation. Group 1: Access cavity was prepared by CT, Group 2: Access cavity was prepared by GE. 3D template and corresponding guide drill were made for group 2 samples after performing optical surface scans. After access cavity preparation, postoperative CBCT scanning was performed for all samples. The amount of tooth structure loss and angle deviation were calculated using Sidexis Software. Statistical Analysis Used: The data were analyzed using IBM SPSS Statistics, version 22. A t-test compared tooth structure loss and angle deviation between groups, and a one-way ANOVA calculated tooth structure loss in multiple directions for both groups (P < 0.001). Results: Our study found that the mean tooth volume loss (17.19 mm3 ± 06.11 standard deviation [SD]) and angle deviation (4.82° ±01.66 SD) in GE was significantly less (P < 0.001) as compared to mean tooth structure loss (38.85 mm3 ± 19.07 SD) and angle deviation (13.16° ±2.34 SD) by CT. Conclusion: GE is more accurate and conservative than CT in management of calcified canals.